New Treatment Options for Refractory/Resistant CMV Infection - Carla Simone Walti; Nina Khanna; Robin K. Avery; Ilkka Helanterä (Transplant International, 2023)
Despite advances in monitoring and treatment, cytomegalovirus (CMV) infections remain one of the most common complications after solid organ transplantation (SOT). CMV infection may fail to respond to standard first- and second-line antiviral therapies with or without the presence of antiviral resistance to these therapies. This failure to respond after 14 days of appropriate treatment is referred to as “resistant/refractory CMV.” Limited data on refractory CMV without antiviral resistance are available. Reported rates of resistant CMV are up to 18% in SOT recipients treated for CMV. Therapeutic options for treating these infections are limited due to the toxicity of the agent used or transplant-related complications. This is often the challenge with conventional agents such as ganciclovir, foscarnet and cidofovir. Recent introduction of new CMV agents including maribavir and letermovir as well as the use of adoptive T cell therapy may improve the outcome of these difficult-to-treat infections in SOT recipients. In this expert review, we focus on new treatment options for resistant/refractory CMV infection and disease in SOT recipients, with an emphasis on maribavir, letermovir, and adoptive T cell therapy.